Water temperature modifies the acute stress response of European sea bass, Dicentrarchus labrax L. (1758). (December 2018) - Samaras, Athanasios; Papandroulakis, Nikos; Lika, Konstadia; Pavlidis, Michail
Abstract: The effects of water temperature (15, 20 and 25 °C) on the stress response of European sea bass, Dicentrarchus labrax, were studied. Blood and water samples were collected prior and at 0.5, 1, 2, 4 and 8 h post-stress for hormonal and biochemical analysis. Water temperature affected the resting concentrations of all stress indicators examined, as well as their response after stress, apart from lactate which response was unaffected by temperature. Cortisol showed the response with the highest outcome at 15 °C, and the fastest at 25 °C. Cortisol release rate in the water was also faster and of higher magnitude at higher temperatures. Glucose had both the fastest and higher in magnitude response at 25 °C, while lactate responded similarly in all temperatures tested. Finally, osmolality changed only at the highest temperature. These results suggest that temperature should be taken into consideration when evaluating the resting levels of stress indicators of European sea bass in laboratory, rearing and field conditions. Additionally, the present results show that temperature affects the stress response, suggesting that fish can differ in their susceptibility to stress depending on the acclimatization temperature. Moreover, it was shown that cortisol release rate in the water, a non-invasive stress indicator, can depict the effects of temperature on cortisol stress response. Highlights: Temperature affects resting levels of commonly used stress indicators in seabass. The profile of physiological stress response is altered by water temperature. Cortisol release rate in the water could explain differences in stress response.